Disrupted neural variability during propofol‐induced sedation and unconsciousness. Issue 11 (4th July 2018) - Huang, Zirui; Zhang, Jun; Wu, Jinsong; Liu, Xiaoge; Xu, Jianghui; Zhang, Jianfeng; Qin, Pengmin; Dai, Rui; Yang, Zhong; Mao, Ying; Hudetz, Anthony G.; Northoff, Georg
Abstract: Variability quenching is a widespread neural phenomenon in which trial‐to‐trial variability (TTV) of neural activity is reduced by repeated presentations of a sensory stimulus. However, its neural mechanism and functional significance remain poorly understood. Recurrent network dynamics are suggested as a candidate mechanism of TTV, and they play a key role in consciousness. We thus asked whether the variability‐quenching phenomenon is related to the level of consciousness. We hypothesized that TTV reduction would be compromised during reduced level of consciousness by propofol anesthetics. We recorded functional magnetic resonance imaging signals of resting‐state and stimulus‐induced activities in three conditions: wakefulness, sedation, and unconsciousness (i.e., deep anesthesia). We measured the average (trial‐to‐trial mean, TTM) and variability (TTV) of auditory stimulus‐induced activity under the three conditions. We also examined another form of neural variability (temporal variability, TV), which quantifies the overall dynamic range of ongoing neural activity across time, during both the resting‐state and the task. We found that (a) TTM deceased gradually from wakefulness through sedation to anesthesia, (b) stimulus‐induced TTV reduction normally seen during wakefulness was abolished during both sedation and anesthesia, and (c) TV increased in the task state as compared to resting‐state during both wakefulness and sedation, but not anesthesia. Together, our results reveal distinct effects of propofol on the two forms of neural variability (TTV and TV). They imply that the anesthetic disrupts recurrent network dynamics, thus prevents the stabilization of cortical activity states. These findings shed new light on the temporal dynamics of neuronal variability and its alteration during anesthetic‐induced unconsciousness.